A PMMA overlayer improving the surface-bound stability of photoanode for water splitting. (20th July 2016) - Zhang, Linlin; Gao, Yan; Ding, Xin
Highlights: A PMMA oligomer coating photoanode for light driven water splitting. The PMMA overlayer was optimized as immersing 2 wt% PMMA in DCM for 15 s. The DS-PEC displayed better long-term stability with the decorated photoanode. Abstract: A PMMA (polymethly methacrylate) oligomer coating photoanode sensitized with the Ru(bpy)3 phosphoric acid derivative1 as photosensitizer and complex2 as water oxidation catalyst was assembled for light driven water splitting. A simple and effective method was optimized by immersing the sensitized photoanode into the DCM solution dissolving 2 wt% PMMA for 15 s. With the decorated photoanode as working electrode, the DS-PEC displayed much better long-term stability, the photocurrent density of which was found to be 0.57 mA/cm 2 after 200 s sustaining light illumination and is four times as high as the undecorated one (0.15 mA/cm 2 ).